2018
DOI: 10.1038/s41598-018-33108-4
|View full text |Cite|
|
Sign up to set email alerts
|

Surfactant/organic solvent free single-step engineering of hybrid graphene-Pt/TiO2 nanostructure: Efficient photocatalytic system for the treatment of wastewater coming from textile industries

Abstract: In this study, hybrid graphene-Pt/TiO2 nanostructure were synthesized by single-step, inexpensive and surfactant/organic solvent free route; hydrothermal technique. The physicochemical properties of hybrid graphene-Pt/TiO2 nanostructure were carefully analyzed by multiple techniques, including X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM). The synthesized hybrid nanostructures were utilized as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 50 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The harmful influence of wastewater treatment affects the whole ecosystem causing damage to the human health, hygiene and all other creatures necessitating the search of green, energy-saving and cost effective water purification methods. Textile wastewater streams are contaminated with aromatic compounds and organic dyes presenting hazard to the environment and therefore are required to be treated before being reused or discharged [134]. To overcome the challenges in wastewater treatment technology, several materials have been explored for application as photocatalyst for degradation of pollutants.…”
Section: Photocatalytic Degradation Of Dyesmentioning
confidence: 99%
“…The harmful influence of wastewater treatment affects the whole ecosystem causing damage to the human health, hygiene and all other creatures necessitating the search of green, energy-saving and cost effective water purification methods. Textile wastewater streams are contaminated with aromatic compounds and organic dyes presenting hazard to the environment and therefore are required to be treated before being reused or discharged [134]. To overcome the challenges in wastewater treatment technology, several materials have been explored for application as photocatalyst for degradation of pollutants.…”
Section: Photocatalytic Degradation Of Dyesmentioning
confidence: 99%
“…Ghouri et al synthesized a series of nanostructured composites of graphene-Pt/TiO 2 and utilized them for the photocatalytic degradation of a methylene blue solution under natural light. 10 These findings indicated that 90% of methyl blue (MB) was eliminated in just 21 minutes. Vahidzadeh et al developed a nanocomposite of nitrogen-doped titanium dioxide-reduced graphene oxide (N-TiO 2 -RGO).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it’s urgently needed to develop a new type of photocatalyst with high pollutant removal capacity. Various strategies have been employed to solve these problems, such as doping with metal or nonmetal elements 5,6 , coupling with semiconductors 7,8 or co-catalysts 9 , and recombination with carbon-based nanomaterials such as carbon nanotubes 10 , graphite oxide (GO) 11,12 , and graphene 13,14 .…”
Section: Introductionmentioning
confidence: 99%